Perspektif Pelayanan Jaminan Kesehatan Nasional (Jkn) Dalam Pandangan Masyarakat di Kecamatan Tikala Kota Manado - Dismo Katiandagho (Poltekkes Kemenkes Padang, 2018)
The purpose of this study was to determine the perspective of the National Health Insurance Service (JKN) in the Community's Views in the Tikala District of Manado City. This type of research is an analytic observational study with a cross sectional study design. The variables of this study are the independent variable level of knowledge, education level, gender and age group, the dependent variable is the benefits of JKN services organized by BPJS Kesehatan. The population and sample in this study were all BPJS Health participants who received JKN services in the Tikala District of Manado City and visited Tikala Health Center in 2014. The number of samples in this study was 73 samples of BPJS Health participants, taken by simple random sampling. The results of this study are related to the benefits of JKN service level of public education (p=0.032), level of knowledge of the community (p=0.033) and not related to the benefits of JKN sex services (p=0.118), age group (p=0.846). , The level of education and knowledge of the community relates to the benefits of JKN services, gender and age group not related to the benefits of JKN services organized by BPJS Health in Tikala District, Manado City